2005
DOI: 10.1007/bf03160903
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the management of dietary supplement use among hospitalized patients

Abstract: Herbs and dietary supplements (HDS) are in widespread use in the United States, and are especially prevalent among chronically ill patients. This population is more likely to be admitted to health care facilities where they may continue to use HDS. The risk of adverse effects from HDS used during admission places significant liability on clinicians and hospitals. We describe the response of health care facilities in the Boston, Massachusetts area to this problem, and propose elements of a hospital policy which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…6 Despite this requirement, nationwide DS hospital policy and practice is plagued with confusion and lack of uniformity. [16][17][18] In addition, curriculum standards for clinicians and trainees are needed because health professional education provides little information on DS administration, knowledge, and interactions. 16 Previous research has examined educational interventions on DS.…”
Section: Discussionmentioning
confidence: 99%
“…6 Despite this requirement, nationwide DS hospital policy and practice is plagued with confusion and lack of uniformity. [16][17][18] In addition, curriculum standards for clinicians and trainees are needed because health professional education provides little information on DS administration, knowledge, and interactions. 16 Previous research has examined educational interventions on DS.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, among patients who use CAM in general, one survey showed that 72% of patients did not report this use to their physicians, 24 and another study found that although two-third of chronically ill patients used dietary supplements, only 30% discussed with their physicians. 25 This highlights that not only is the use of CAM pervasive but also that its utilization is not discussed with the medical team in pediatrics or adult population and that its use is not rooted in evidence-based medicine, rather due to cultural, religious, or personal practices. Additionally, physicians are not equipped with the resources or knowledge of the role of CAM in order to disuses its utility in neuro-oncological care; however, the burden of decision-making and discussion of such modalities is in large left to the team of physicians caring for patient.…”
Section: Discussionmentioning
confidence: 99%
“…In creating their policies, many hospitals have struggled with balancing patient-centered care with legal and ethical concerns over DS use. 7,15,16 In the JCHAO Comprehensive Accreditation Manual for Hospitals, a medication is defined as "any prescription medication, sample medication, herbal remedies, vitamins, nutraceuticals, over the counter drugs, vaccines, diagnostic and contrast agents, used on or administered to person to diagnosis, treat, or prevent disease or other abnormal conditions . .…”
Section: Discussionmentioning
confidence: 99%
“…7 Currently, there is no universally accepted guideline for managing a patient's DSs in the pediatric hospital setting. 5 However, both the Joint Commission Accreditation of Healthcare Organizations (JCAHO) and American Health System Pharmacists offer standards and guidelines on the use of DSs in hospitals.…”
Section: What's Known On This Subjectmentioning
confidence: 99%